The Effect of a Novel Serine Protease Inhibitor on Inflammation and Intestinal Permeability in a Murine Colitis Transfer Model - Van Spaendonk, Hanne; Ceuleers, Hannah; Smet, Annemieke; Berg, Maya; Joossens, Jurgen; Van der Veken, Pieter; Francque, Sven M.; Lambeir, Anne-Marie; De Man, Joris G.; De Meester, Ingrid; Augustyns, Koen; De Winter, Benedicte Y. (Frontiers in Pharmacology, 2021)
Background A protease/antiprotease disbalance is observed in inflammatory bowel disease (IBD). We therefore studied the effect of the novel serine protease inhibitor UAMC-00050 on intestinal inflammation and permeability in a chronic colitis T-cell transfer mouse model to get further insight into the regulation of T cell-mediated immunopathology. Methods Colitis was induced in severe combined immunodeficient (SCID) mice, by the adoptive transfer of CD4+CD25-CD62L+ T-cells. Animals were treated intraperitoneally (i.p.) 2x/day with vehicle or UAMC-00050 (5 mg/kg) from week 2 onwards. Colonic inflammation was assessed by clinical parameters, colonoscopy, macroscopy, microscopy, myeloperoxidase activity and cytokine expression levels. At week 4, 4kDa-FITC-dextran intestinal permeability was evaluated and T helper transcription factors, protease-activated receptors and junctional proteins were quantified by RT-qPCR. Results Adoptive transfer of CD4+CD25-CD62L+ T-cells resulted in colonic inflammation and an altered intestinal permeability. The serine protease inhibitor UAMC-00050 ameliorated both the inflammatory parameters and the intestinal barrier function. Furthermore, a decrease in colonic mRNA expression of T-bet and PAR4 was observed in colitis mice after UAMC-00050 treatment. Conclusions The beneficial effect of UAMC-00050 on inflammation was apparent via a reduction of Tbet, IFN-γ, TNFα, IL-1β and IL-6. Based on these results, we hypothesize a pivotal effect of serine protease inhibition on the Th1 inflammatory profile potentially mediated via PAR4.